Peran Tim Siaga Bencana Berbasis Masyarakat (SIBAT) dalam Kesiapsiagaan Bencana di Kecamatan Sumberjambe Kabupaten Jember (The Role of Community-Based Disaster PreparednessTeam in Disaster Preparedness in Sumberjambe Subdistrict Jember Regency) - Indira Karina Parahita; Novia Luthviatin; Erdi Istiaji (Pustaka Kesehatan, 2016)
Many regions in Indonesia have potency to occur disaster every time including JemberRegency. Community-Based Disaster Preparedness Team is one of PMI’s programs asdisaster preparedness effort. The most active of Community-Based DisasterPreparedness Team in Jember Regency is Community-Based Disaster PreparednessTeam of Sumberjambe Subdistrisct. This research is purposed to know the role ofCommunity-Based Disaster Preparedness Team in disaster preparedness inSumberjambe Subdistrisct Jember Regency. This research is descriptive research withqualitative approachment locating in Sumberjambe Subdistrisct Jember Regency. Theinformants of research were determinded by snowball sampling and purposive samplingtechnique. The informants were obtained 6 persons, there were a key informant(coordinator of Community-Based Disaster Preparedness Team in Jember Regency), 3main informants (Community-Based Disaster Preparedness Team Team ofSumberjambe Subdistrict and Head of Social Prosperousness in SumberjambeSubdistrict), and 2 additional informants (Sumberjambe Subdistrict people). Data weregathered by in-depth interview, triangulation, and documentation. The result of researchshowed that Community-Based Disaster Preparedness Team had roles as escort,adviser, instructor, and motivator in disaster preparedness in Sumberjambe Subdistrict.Community-Based Disaster Preparedness Team was not only as a communityempowerment, but the advocacy could also be found in their programs/events.Keywords: Role, Community-Based Disaster Preparedness Team, Disasterpreparedness